2015
DOI: 10.1186/s13037-015-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bupivacaine soaked gauze in postoperative pain relief in laparoscopic cholecystectomy: a prospective observational controlled trial in 120 patients

Abstract: BackgroundSymptomatic gallstone disease is one of the most common problem attended by a general surgeon. The application of minimally invasive surgical techniques for the removal of gallbladder is now an accepted and preferred method for treating this condition. The avoidance of a subcostal incision and minimal bowel handling leads to decreased postoperative pain, early returning to function and overall shorter duration of hospital stay. Nevertheless, patients do have significant postoperative pain, and newer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…8 Other studies have stated that the largest component in abdominal pain is formed by the parietal peritoneum, which is derived from the incision site, followed by pneumoperitoneum and surgical procedures such as cholecystectomy. 7,12 Pain caused by the surgical incision has been thought to be the most important component and has been shown to be more intense than visceral pain during the first 48 hours after laparoscopic cholecystectomy. 13 Although some studies have shown that injection of a local anaesthetic agent to trocar entry sites does help pain relief, other studies did not attempt to show a positive association with regard to pain relief and have suggested that parietal pain does not contribute substantially to the total pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other studies have stated that the largest component in abdominal pain is formed by the parietal peritoneum, which is derived from the incision site, followed by pneumoperitoneum and surgical procedures such as cholecystectomy. 7,12 Pain caused by the surgical incision has been thought to be the most important component and has been shown to be more intense than visceral pain during the first 48 hours after laparoscopic cholecystectomy. 13 Although some studies have shown that injection of a local anaesthetic agent to trocar entry sites does help pain relief, other studies did not attempt to show a positive association with regard to pain relief and have suggested that parietal pain does not contribute substantially to the total pain.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder pain is frequent in the postoperative period, and is thought to be related to residual carbon dioxide. 6,7 Studies of pain mechanisms are usually based on somatic rather than visceral nociception. However, more complications are associated with accessing visceral structures, with adequate visceral stimuli studied in research models.…”
Section: Introductionmentioning
confidence: 99%
“…A symptomatic gallstone disease is one of the prevailing problems seen in clinical practice [1]. Surgical removal of the gall bladder can be done laparoscopic or open cholecystectomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Progressive manner to further reduce this pain are the subject of many ongoing studies. Intraoperative and postoperative techniques for diminishing postoperative pain have been expressed [1]. Better control of postoperative pain can benefit L.C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation